Development of methods for dynamic distribution of parameters to produce products in light industry - Островерх, Елена Юрьевна (Technology audit and production reserves, 2015)
Universal distribution function of anthropometric characteristics, that taking into account the real according to different consumer groups is constructed. This function is used for program planning output of light industry, which is complicated by a wide variety of types and sizes of products, which in turn is caused by a variety of anthropometric consumers of these products. The resulting distribution function allows to find integrated parameters, which allow to predict the total number of products. Application of non-uniform distribution function allows us to calculate the percentage of different sizes based on the most complete software market. Rational production capacity at the same time can be determined based on the integrated dependency falling into a given size range. percentages for different groups are recommended on the base of the size of the existing classification of light industry products. The results allow to determine the percentages of sizes and plan accordingly output in accordance with the real needs of consumers.